Lockdown in a specialised rehabilitation unit: the best of times. (21st September 2020) - Glancy, D.; Reilly, L.; Cobbe, C.; Glynn, M.; Punchoo, S.; Foy, K.
Abstract : Specialised rehabilitation units offer inpatient multi-disciplinary rehabilitation for individuals with severe and enduring mental illness. A cornerstone of therapy is the work in the community through further education and community organisations. However, coronavirus restrictions have meant that such external supports are no longer available for the duration of the crisis. This has led to opportunities for developing new ways of offering rehabilitation within hospital environments. This article describes some of the new initiatives developed. The benefits of the lockdown for service users are also discussed. Many found the cessation of visits from family members with whom they had an ambivalent relationship helpful. The lockdown improved relationships between patients on the unit and encouraged a greater feeling of community. The lockdown has also emphasised the importance of team self-awareness and an awareness of the nature of the treatments offered.